Extreme points and convolution properties of some classes of multivalent functions - O. P. Ahuja (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the extreme points of closed convex hulls of the classes of multivalent functions related to Ruscheweyh derivatives and then these are used to determine the coefficient bounds. Finally, we investigate convolution conditions and other properties of the functions in these classes.